Teaching practices mediating the effect of teachers’ psychological stress, and not physiological on their visual focus of attention - Chaudhuri, Saswati; Jõgi, Anna-Liisa; Pakarinen, Eija; Lerkkanen, Marja-Kristiina (Frontiers in Education, 2023)
The aim of the present study was to investigate the association between teachers’ (N = 53) physiological and psychological stress and their visual focus of attention as well as the mediating effect of teaching practices on this association in authentic classroom settings. Data were collected using multimodal methods of measurement: salivary cortisol levels for physiological stress, a self-reported questionnaire for psychological stress, observed teaching practices during one school day, and eye-tracking video recordings of classroom teachers during one lesson for teachers’ visual focus of attention. The results showed that neither teachers’ physiological nor psychological stress was directly related to their visual focus of attention. However, using more child-centered teaching practices compared with teacher-directed ones was related to a higher number of fixations on students, longer total fixation duration, and more individualized distribution of visual focus of attention on students. Teacher’s teaching practices mediated the effect of teachers’ psychological stress on their fixation counts on students and distribution of visual focus of attention. The results suggest that teaching practices are related to the visual attention teachers’ give to students and that teachers’ stress affects their visual focus of attention through teaching practices. The practical implications of this study suggest that teachers should receive training and support to recognize their stress level and its association with their teaching.